EVALUASI PERAN PENYULUH PERIKANAN TERHADAP KELOMPOK PEMBUDIDAYA IKAN KARAMBA JARING APUNG (KJA) DI KOLAM BEKAS TAMBANG DI KELURAHAN LOK BAHU KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA - Dewiherawati Salu; Helminuddin; Elly Purnamasari (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
This research was aimed at knowing the extension officer’s activity towards the fish farmer group with floating-net-cages in ex-mining ponds in Lok Bahu Urban Village and knowing the role of the extension officers who were assigned in Lok Bahu Urban Village, Sungai Kunjang District, Samarinda, in encouraging the fish farmer group. This research was conducted for 5 months starting from August 2018 to December 2018. In this case, the research location was in Lok Bahu Urban Village, Sungai Kunjang District, Samarinda. Sampling was done based on a census method that was all fish farmer groups of Rawa Bening 1 and Rawa Bening 2 were the respondents of this research. The research finding showed that the fisheries extension officer’s role in encouraging the fish farmer group with floating-net-cages in ex-mining ponds was classified in a maximum high category. Therefore, the three indicators of fisheries extension officer’s role that should be improved are the extension officer’s role in transmitting the Technology and Science, in business activity and in transmitting information and innovation.